Geochemical fields of trace elements of landscape the alpine region of the Greater Caucasus - Tatyana Vasilyevna Degtyarova; Viktor Aleksandrovich Shalnev (Наука. Инновации. Технологии, 2022)
The analysis of term review of geochemical field and introduces the concept of geochemical field component of the landscape. Geochemical field of trace elements in rocks and soils examined on the example of mountainous physiographic region of the northern slope of the Greater Caucasus. Based on the analysis of the geochemical specifics of bedrock allocated lithogeochemical field of trace elements with the side of the Main Caucasian ridge and the Front Range. We consider the territorial differentiation component pedogeochemical fields micronutrients Laba-Teberda, Elbrus-Teberdino and the Terek-Kuban landscape districts, which revealed a similar spatial structure in the distribution of trace elements in soils for landscaping altitude belts. According to the predominant factor in the formation characteristics of distribution of trace elements in the landscape of high-altitude zones are marked genetic groups (organo-mineral, nutrient-leaching and nutrient-capacious) component pedogeochemical trace ields.